The Law of Jealousy Anthropology of Sotah - Destro, Adriana (Brown Judaic Studies, 2020)
This book applies anthropological insights to the understanding of an ancient and puzzling ritual, that of the sotah, or suspected adulteress. The ritual, initiated by a suspicious husband, was first described in Numbers 5, is elaborated by the later rabbis. Destro argues that the rabbis patter the sotah ritual to emphasize its, and the woman's, anomalous nature and the symbolic work that this patterning does for the rabbinic system as a whole.